Inclusão digital no Brasil - ALBIERI, André Luis Villa (004, 2005)
O termo inclusão digital ou uso já foi transformado em jargão. É comum ver empresas e governos falando em democratização do acesso e da inclusão digital sem critérios e dando atenção se essa inclusão promove o efeito desejado. impostos, burocracia, educação para facilitar o acesso aos computadores.

The term digital incluision of so using already was changedded into a jargon. It is cammon to see compies and governements speaking in democratization of the access and digital inclusion witout criteria and givin attention if to such inclusion promotes the effect desired.The probemis that turned fashion to speak of the subject , still in Brazil, with as many difficultiesm taxes, bureaucracy, education to facilitate the acesss to the computers.
Digital inclusion in Brazil
Keywords: Inclusão social; Informação e Comunicação